'Standard THC units': a proposal to standardize dose across all cannabis products and methods of administration. (9th December 2019) - Freeman, Tom P.; Lorenzetti, Valentina
Abstract: Background and Aims: Cannabis products are becoming increasingly diverse, and vary considerably in concentrations of ∆ 9 ‐tetrahydrocannabinol (THC) and cannabidiol (CBD). Higher doses of THC can increase the risk of harm from cannabis, while CBD may partially offset some of these effects. Lower Risk Cannabis Use Guidelines currently lack recommendations based on quantity of use, and could be improved by implementing standard units. However, there is currently no consensus on how units should be measured or standardized among different cannabis products or methods of administration. Argument: Existing proposals for standard cannabis units have been based on specific methods of administration (e.g. joints) and these may not capture other methods, including pipes, bongs, blunts, dabbing, vaporizers, vape pens, edibles and liquids. Other proposals (e.g. grams of cannabis) cannot account for heterogeneity in THC concentrations among different cannabis products. Similar to alcohol units, we argue that standard cannabis units should reflect the quantity of primary active pharmacological constituents (dose of THC). On the basis of experimental and ecological data, public health considerations and existing policy, we propose that a 'standard THC unit' should be fixed at 5 mg THC for all cannabis products and methods of administration. If supported by sufficient evidence in future, consumption of standard CBD units might offer an additional strategy for harm reduction. Conclusions: Standard ∆ 9 ‐tetrahydrocannabinol (THC) units can potentially be applied among all cannabis products and methods of administration to guide consumers and promote safer patterns of use.